Analysis of importance level and quality achievement aspect in dental health service (A case study on Waru Sidoarjo Community Dental Health Service) - Taufan Bramantoro; Retno Palupi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Patients as customers of health services actually have expectation and assessment of health services perceived. During the initial interview conducted at Waru Sidoarjo Community Dental Health Service (Waru Sidoarjo CDHS), it is known that one hundred percent of initial respondents were not satisfied with dental care service provided. All of those respondents assessed that Waru Sidoarjo CDHS still has not met their expectations of service quality factors considered to be important for them. It is even known that there is usually a gap between the expectations of quality dental care service and the assessment of services perceived. As a result, further researches are needed to be conducted regarding the level of importance and achievement-related with factors that affect the quality of health services. Purpose: The purpose of this study was to determine the level of importance and achievement of the quality aspects of the health service provided by Waru Sidoarjo CDHS. Methods: This study can be considered as a descriptive observational study. The instrument used in this study was measurement instruments of service quality. Respondents in the study were 200 patients who visited to dental care services in Waru Sidoarjo CDHS in July 2011. Results: All of the attributes had a mean value of dominant importance and assessments at four. The attributes of the appearance feasibility of medical staffs had the highest interest, about 4.780. Meanwhile, the mean value of the lowest importance was on the attributes of the service suitability, about 4.595. During the observation of the service value, it is also known that the highest mean value was on the non-discriminative services, about 4.600. Conclusion: It can be concluded that there were attributes considered to be important for patients, but still not being fully met by health services provided by the service provider or Community Dental Health Care. Those attributes involving waiting room comfort, service readiness and service preparation attributes which not only had high importance value, but also had a large percentage of respondents who were not satisfied.Latar belakang: Pasien sebagai pengguna jasa pelayanan kesehatan, memiliki harapan dan penilaian terhadap pelayanan kesehatan yang diterima. Pada wawancara awal yang dilakukan pada pasien Balai Pengobatan Gigi Puskesmas Waru Sidoarjo, didapatkan bahwa seratus persen responden awal merasa tidak puas dengan pelayanan kesehatan gigi. Seluruh responden awal menilai pihak BPG Puskesmas belum memenuhi harapan mereka terhadap faktor kualitas pelayanan yang mereka nilai penting. Terdapat kesenjangan antara harapan mereka terkait kualitas pelayanan kesehatan gigi yang mereka nilai penting dengan penilaian mereka terhadap pelayanan yang diterima, sehingga diperlukan penelitian lebih lanjut mengenai tingkat kepentingan dan pencapaian terkait faktor yang berpengaruh terhadap kualitas pelayanan kesehatan. Tujuan: Tujuan penelitian ini adalah untuk mengetahui tingkat kepentingan dan pencapaian aspek kualitas pelayanan yang diberikan Balai Pengobatan Gigi Puskesmas Waru Sidoarjo. Metode: Penelitian ini merupakan penelitian deskriptif observasional. Instrumen yang digunakan pada penelitian ini adalah instrumen pengukuran kualitas pelayanan jasa. Responden pada penelitian adalah 200 pasien yang berkunjung dan mendapatkan pelayanan kesehatan gigi di Balai pengobatan Gigi Puskesmas Waru Sidoarjo pada bulan Juli 2011. Hasil: Seluruh atribut memiliki rerata nilai kepentingan dan penilaian yang dominan pada nilai 4. Atribut kelayakan penampilan staf medis memiliki nilai kepentingan tertinggi sebesar 4,780. Rerata nilai kepentingan terendah pada atribut kesesuaian layanan sebesar 4,595. Pada pengamatan nilai penerimaan layanan, rerata nilai tertinggi pada atribut layanan yang tidak diskriminatif sebesar 4,600. Rerata nilai terendah didapatkan pada atribut kesiapan layanan sebesar 4,200. Kesimpulan: Disimpulkan bahwa terdapat atribut yang dinilai penting tetapi belum sepenuhnya terpenuhi oleh pelayanan kesehatan yang diberikan oleh penyedia layanan atau Puskesmas. Atribut kenyamanan ruang tunggu, kesigapan layanan, dan kesiapan layanan, memiliki nilai kepentingan yang tinggi, tetapi memiliki nilai persentase yang besar pada jumlah responden yang merasa tidak puas.